(untitled) (Journal of the College of Basic Education, 2023)
The aim of this work is to study the effect of gamma radiation on some rheological and optical properties of Polyacrylamide in ethylene glycol. The polymer irradiated with gamma rays to 127 and 254 (rad/min) for 10 minutes on a disk shape samples. The rheological parameters (shear, Relative, specific, reduced, and Intrinsic viscosity), Average viscosity number molecular weight and Effective molecular radius, in addition, the optical parameters Absorbance, refractive index, Molar absorption coefficient, Reflectivity, Coefficient of finesse and Specificreflectance were studded.The obtained results show decrease in (shear-relative-specific-reduced) viscosities, average viscosity molecular weight, original viscosity on other hand there is disparity in the values of effective molecular radius, absorption coefficient, refractive index, reflectivity coefficient of finesse, and specific reflectance as the dose increases. The results show that radiation dose has effective influence on polymer chemical structure therefore its properties will be a function of radiation dose.